2022
DOI: 10.1002/ab.22027
|View full text |Cite
|
Sign up to set email alerts
|

Facial width‐to‐height ratio predicts fighting success: A direct replication and extension of Zilioli et al. (2014)

Abstract: Zilioli et al. (2014) were the first to show an association between male facial width-toheight ratio (fWHR) and physical aggression and fighting ability in professional mixedmartial-arts fighters. Here, we re-examined this relationship by replicating (using all original measures) and extending (using 23 new variables related to fighting performance) Zilioli et al. (2014) in a statistically well-powered sample of 520 fighters using automatic and manual measures of the fWHR involving both eyelid and eyebrow land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…(2015) (Caton, Hannan, et al, 2022), and thus tangentially also of our previous work (Třebický et al, 2015) that tested the association between facial width-to-height ratio and fighting success (but cf. also a recent preprint by .…”
Section: Introductionmentioning
confidence: 90%
“…(2015) (Caton, Hannan, et al, 2022), and thus tangentially also of our previous work (Třebický et al, 2015) that tested the association between facial width-to-height ratio and fighting success (but cf. also a recent preprint by .…”
Section: Introductionmentioning
confidence: 90%
“…Caton, Pearson, & Dixson, 2022). More specifically, these men are proficient grapplers (Caton, Hannan, & Dixson, 2022).…”
Section: Formidability As Men’s Social Capitalmentioning
confidence: 99%
“…This allocation of status could similarly emerge from their success in combat sports. Professional wrestling began as actual contests from the remnants of folk-style wrestling (e.g., catch-as-catch can and Greco-Roman), which could have unsurprisingly seen formidably faced men having advantages (Caton, Hannan, & Dixson, 2022). As professional wrestling became scripted in the Early 20th Century, promoters could have used this understanding in scripting their shows to draw audiences based on who appeared to be more competent as a wrestler 1 .…”
Section: Formidability As Men’s Social Capitalmentioning
confidence: 99%
“…Facial width-to-height ratio (fWHr) has gained extensive attention as a putatively sexually-dimorphic trait, with numerous studies confirming the relationship between fWHr and individual behavior induced by psychological traits. Previous studies have revealed several fWHr-associated behaviors including risk-taking [ [1] , [2] , [3] ], aggression [ [4] , [5] , [6] ], dominance [ 7 , 8 ], aiming for success [ [9] , [10] , [11] ], antisocial behavior [ [12] , [13] , [14] ] and humanness [ 15 ], which have primarily focused on social and economic fields. However, there is not much research on whether fWHr is relevant to political decision-making, specifically, political risk-taking behaviors.…”
Section: Introductionmentioning
confidence: 99%